Examining the presence of social intelligence in job interviews through multimodal social semiotic analysis - Mimi Nahariah Azwani Mohamed,; Salleh Talib,; Fazita Md Tab,; Salawati Ahmad,; Elizabeth M. Anthony,; Azizi Basar,; Shakina Shahlee,; Geeva Samynathan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Graduates with high level of social intelligence are in high demand. Those who can demonstrate having good attitude and social flexibility, able to build good relationships with others, and able to use appropriate language during their interviews have higher chances of being employed. However, reports show that graduates of higher learning institutions lack social intelligence. Failure to address this issue can affect future graduates’ employability. This paper examined the extent to which students in higher learning institutions had developed social intelligence. The participants were the final year students of one technical university in Malaysia. These participants underwent a job interview session as one of their course assessments. In this paper, the responses by three participants were selected to be analysed. The mock job interview sessions, which were conducted online, were recorded and transcribed.The data were analysed using multimodal social semantic discourse analysis to determine the candidates’ intention and then, using the five dimensions of social intelligence which included social awareness, presence, authenticity, clarity, and empathy to examine the presence (absence) of social intelligence. It was found that social awareness and empathy to build relationships and develop trust with the interviewer were taken for granted by the participants. In addition, the participants’ focused more on the qualification and skills that they had rather than how they could use their skills for the benefit of a company or organisation. The findings provided invaluable input on ways in designing courses that promote the development of social intelligence among students of higher learning institutions.